Stability Analysis of Replacement Material in Dam Body at Meninting Dam - Wildan Faris Alamudi; Indra Nurtjahjaningtyas; Luthfi Amri Wicaksono (Rekayasa Sipil, 2025)
Embankment material in dam construction is an important aspect that needs to be considered. The lack of embankment material around the dam is a problem in the Meninting Dam construction project, so it uses materials outside the dam area. With the change in the embankment material used, research is needed on the stability of the dam body. This study aims to determine the characteristics of the replacement material, seepage capacity, uplift force, and slope stability safety factor at the dam. Physical tests are used to determine the physical characteristics of the soil (moisture content, soil specific gravity, rock specific gravity, soil plasticity index filter analysis), while the mechanical test is performed to determine the soil's movement, strength, stiffness, and deformation. This study also uses software assistance, such as Geostudio from Rockscience slide, to calculate a slope's stability level. The results showed that the value of the safety factor obtained on the upstream slope without earthquake is 3.463, the upstream slope with OBE earthquake is 2.057, the upstream slope with MDE earthquake is1.588, the downstream slope without earthquake is 3.117, the downstream slope with OBE earthquake is 2.288, downstream slope with MDE earthquake is 1.898. The value of the safety factor is declared safe because the value obtained is >1.5 conditions without an earthquake and >1.2 conditions with an earthquake. The uplift value on every equipotential is 10.58 t/m2. The value of seepage capacity that comes out downstream of the dam is 4,529 x 10-5 m3- seconds. Seepage capacity is said to be safe because < 0.0127 m3- seconds. The lack of stone material as the main constituent of dam deposits in the research area is the main factor in this study, which focuses on finding the value of the safety factor, lifting force, and seepage capacity of the replacement material for dam deposits. This research will use soil-filling material as a substitute for the Constituent stones, which are very limited in number at the research site.